Muslim cadre education and its role in shaping religious authority in 19th-Century West Java - Nurjaman, Andri; Witro, Doli; Alamin, Nurul; Alghani, Raid; Yusuf, Muhamad (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2025)
This article investigates the Muslim cadre education and its role in shaping religious authority in nineteenth-century West Java through the case of KH Ahmad Syatibi Al-Qonturi and his pesantren (Islamic boarding school). This study conceptualises religious authority as a socially produced legitimacy sustained through epistemic credibility, moral exemplarity, and networked reproduction. The research employs a qualitative historical design, based on documentary sources, and applies qualitative data analysis procedures, including data condensation, data display, and conclusion drawing. The findings indicate that Mama Syatibi developed a pesantren-based infrastructure for Muslim cadre education that contributed to the consolidation of religious authority in West Java. This model of Muslim cadre education operated through three interconnected practices: regular teaching and recitation, da‘wah bil qalam (preaching with the pen) through extensive written works, and a role model as embodied moral discipline. These practices strengthened authority by making interpretive competence publicly verifiable, stabilising knowledge transmission through texts, and reinforcing communal trust through exemplary conduct. Moreover, the diffusion of his students —many of whom became Muslim scholars and founded or led pesantren across West Java— demonstrates how Muslim cadres reproduced religious authority through educational succession and institutional multiplication. The study contributes to scholarship on Islamic education and leadership by showing how pesantren-based education and training shaped religious authority in the West Javanese context from the nineteenth to the early twentieth century.